Weight Loss and the Older Adult: Risks and Benefits - Wendy Gans; Rachel L. Savelle; Nancy J. Gal; Wendy J. Dahl (EDIS, 2020)
Adults who are obese are often advised to lose weight to reduce the risk of chronic disease. However, the health benefits of weight loss change as we become older, and unintentional weight loss is linked to its own set of health risks. This new 3-page publication of the UF/IFAS Food Science and Human Nutrition Department discusses the risks and benefits of planned and unplanned weight loss for older adults. Written by Wendy Gans, Rachelle Savelle, Nancy J. Gal, and Wendy Dahl. https://edis.ifas.ufl.edu/fs401